Neural Correlates of Time Versus Money in Product Evaluation - Lehmann, Sebastian; Reimann, Martin (Frontiers in Psychology, 2012)
The common saying “time is money” reflects the widespread belief in many people’s everyday life that time is valuable like money. Psychologically and neurophysiologically, however, these concepts seem to be quite different. This research replicates prior behavioral investigations by showing that merely mentioning “time” (compared to merely mentioning “money”) leads participants to evaluate a product more positively. Beyond this finding, the present functional magnetic resonance imaging (fMRI) experiment provides novel insight into the neurophysiological underpinnings of this behavioral effect by showing that more positive product evaluations in the time primes (compared to money primes) are preceded by increased activation in the insula. Our data, therefore, support the idea of a time mindset that is different from a money mindset. Studies on the functional neuroanatomy of the insula have implicated this brain area in distinct but related psychological phenomena such as urging, addiction, loss aversion, and love. These functions imply greater personal connection between the consumer and a target subject or object and, thus, help explain why time-primed consumers rate products more positively.